Adsorption Studies of Cu from Aqueous/Acidic Solutions on to Bentonite - Artur P. Terzyk (Adsorption Science & Technology)
The influence of temperature on the adsorption of 4-hydroxyacetanilide (paracetamol) from aqueous solution (pH = 7) on to de-ashed, commercial activated carbons is described. Three carbon samples, D43/1 (Carbo-Tech. Essen, Germany), WD-extra and AHD (Hajnówka, Poland), were investigated. They were de-ashed and characterised using low-temperature nitrogen adsorption, porosimetry and Bachmann's method, as well as by different theoretical approaches. Carbon surface properties were characterised by the method of Boehm and the enthalpy of immersion in water. The adsorption/desorption isotherms of paracetamol in the temperature range 300–320 K were measured together with the enthalpy of immersion in paracetamol solution. The carbon adsorption properties towards paracetamol are discussed. Relationships describing the dependence of adsorbability on the temperature are proposed as well as the dependence of the relative enthalpy of adsorption on the concentration of basic carbon surface groups.